2021
DOI: 10.1186/s12889-021-12252-z
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in the utilization of HIV counseling and testing services among undergraduates in mainland China

Abstract: Background HIV counseling and testing (HCT) is provided free of charge on college campuses, but very few studies have examined whether HCT uptake is equitably distributed. This cross-sectional study aimed to compare the relative importance of various determinants of HCT uptake among undergraduates in mainland China so as to assess and subsequently to suggest ways to eliminate inequities in its use, guided by the Andersen’s behavioral model. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…In our study, the finding might be explained by the high incidence of sexual behavior and unsafe sexual behavior among male students, and male students have a higher risk perception and behavior initiative [ 55 , 56 ]. Secondly, the medical students were related to higher willingness to HIV testing, which was similar to the other study [ 15 ]. Medical students have more opportunities to receive medical-related information, thereby developing stronger awareness of HIV prevention and treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, the finding might be explained by the high incidence of sexual behavior and unsafe sexual behavior among male students, and male students have a higher risk perception and behavior initiative [ 55 , 56 ]. Secondly, the medical students were related to higher willingness to HIV testing, which was similar to the other study [ 15 ]. Medical students have more opportunities to receive medical-related information, thereby developing stronger awareness of HIV prevention and treatment.…”
Section: Discussionsupporting
confidence: 85%
“…For example, a free HIV counseling and testing (HCT) and an anonymous urine self-collection for HIV self-testing (HIVST) are provided on college campuses [ 13 , 14 ]. Unfortunately, due to the lack of HIV testing knowledge, discriminatory attitudes and HIV-related stigma, the utilization rate of these services are low of Chinese college students [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wechat and Sina Weibo, as the largest social media platforms, were also used to distribute questionnaires to improve sample representativeness. A detailed description of the study design and settings was demonstrated in our previous publications [ 12 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Anderson's Behavioural Model [ 11 ] has been adapted to elucidate the factors contributing to risk discordance. According to this model, the decision to undergo HIV testing is affected by three sets of factors: predisposing, enabling and need characteristics [ 12 ]. Predisposing characteristics include sociodemographics {e.g., gender [ 12 ], sexual orientation [ 12 ], major [ 12 ], grade/age [ 12 , 13 ], race [ 2 ], occupation [ 8 ], age at first sex [ 1 , 8 , 14 ]} and AIDS-related knowledge-attitude-belief -practice (KABP) such as knowledge of HIV transmission [ 1 , 12 ], stigma against people living with HIV (PLHIV) [ 12 ] and prior testing [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation